An Efficient and Practical Method for the Synthesis of Saxagliptin Intermediate 2-(3-Hydroxy-1-adamantane)-2-oxoacetic Acid and Its Optimization - Qi Liao; Lan Jiang; Cong Li; Yaling Shen; Min Wang; Chengkun Cao; Xiangnan Hu (Journal of Chemistry)
A mild and relatively simple way for preparation of 2-(3-hydroxy-1-adamantane)-2-oxoacetic acid (I) was reported. It was prepared from 1-adamantanecarboxylic acid (II) via sulfuric acid/nitric acid to get 3-hydroxy-1-adamantanecarboxylic acid (III); treated with the one-pot method through acylation, condensation, and decarboxylation to obtain 3-hydroxy-1-acetyladamantane (IV); and finally oxidized by potassium permanganate (KMnO4) to get the target compound (I). The overall yield was about 60%, which provides a new idea for commercial production of saxagliptin intermediate.